Usage pédagogique des ressources éducatives libres : quelles tensions entre ouverture et didactisation des ressources numériques ? - Luc Massou (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
This invited text looks at the obstacles currently identified in the use and re-appropriation of open educational resources (OER) by teachers, for which the balance is sometimes complex to find between opening up digital resources to the widest possible audience of users and the didactic choices made when the resource itself was designed. In a more global way, this problematic questions the consideration of didactic transposition–which is one of the components of the school and university form–in digital resources shared within an educational community, and its impact on the potential uses of these OER and their re-appropriation on a larger scale.